Influence of Tokar Gap wind jet on latent heat flux of Central Red Sea: empirical orthogonal function approach (Ocean and Coastal Research, 2024)
The aim of this study was to investigate the main factors that influence the latent heat fluxes (LHF) in theTokar Gap in the central part of the Red Sea. From 2000 to 2020, ERA5 reanalysis data on summer months ofthe Central Red Sea were used to match the time when the Tokar Wind Jet appeared. The diurnal variabilityof the Tokar Gap peaks in the early morning. The time series data of the wind speed showed that the TokarWind Jet appeared from July to August. The empirical orthogonal functions (EOF) analysis method was usedto determine the modes of LHF variabilities. The sum of the first two modes of variability explained ~ 90.8% ofthe total variance. The first mode explained 80.8%, whereas the second mode represented approximately 9.9%.To examine the contribution of sea surface temperature (SST) and wind speed to the first two EOF principalcomponents, the correlation coefficient and determination coefficient were applied. The results showed that SSThad a CC of 0.90 and a DC of 81.99%, whereas wind speed showed a CC of 0.35 and a DC of 12.80%. Theseresults may be explained by the strong link between SST and the specific humidity differences of saturation andactual vapor pressure. Partial correlation results indicate that there is an indirect relation between wind and LHF.In this study SST was the dominant factor, influencing LHF variability in the study area.